New Directions in Spiritual Kinship : Sacred Ties across the Abrahamic Religions - Thomas, Todne; Malik, Asiya; Wellman, Rose (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This volume examines the significance of spiritual kinship-or kinship reckoned in relation to the divine-in creating myriad forms of affiliations among Christians, Jews, and Muslims. Rather than confining the study of spiritual kinship to Christian godparenthood or presuming its disappearance in light of secularism, the authors investigate how religious practitioners create and contest sacred solidarities through ritual, discursive, and ethical practices across social domains, networks, and transnational collectives. This book's theoretical conversations and rich case studies hold value for scholars of anthropology, kinship, and religion. .
Keywords: Social sciences.; Religion and sociology.; Ethnology.; elektronické knihy; electronic books